Representasi Makna Gaya Kepemimpinan Otoriter Tokoh Thomas Shelby dalam Film Serial Peaky Blinders - Mochammad Fajar Adityansyah; Dede Lilis Chaerowati (UNISBA Press, 2023)
Abstract. A leader usually has a communication style that is quite interesting and unique according to his own leadership style. Leadership is a person's ability to influence other people to do something with the goals to be achieved. There is one character in a serial film called 'Peaky Blinders' that fulfills the criteria of being a leader as it should be, that character is Thomas Shelby. This study is entitled